An empirical investigation: The impact of audit learning types on students' confidence and competence during the COVID-19 Pandemic era - Syamsuri Rahim; Muhammad Suun; Siti Nurhayani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The primary aim of this study is to examine the practical effects of various forms of audit learning, including synchronous learning, asynchronous learning, and blended learning, on students' levels of confidence and competence throughout the COVID-19 pandemic timeframe. This study employs a quantitative research strategy that incorporates primary data collection methods. The research sample comprised accounting students enrolled at Universitas Muslim Indonesia Makassar in 2019. The methodology employed involves utilizing multiple linear regression analysis with the assistance of SPSS software version 22. The results of this study demonstrate that the variables related to the kind of audit learning, such as synchronous learning, asynchronous learning, and blended learning, have a statistically significant influence on the degree of competency students exhibit. The impact of various learning modalities, including synchronous, asynchronous, and blended learning, on the self-assurance of female students is significant and warrants further investigation. The results of this study indicate that various methods of acquiring knowledge, such as synchronous, asynchronous, and hybrid approaches, significantly influence students' levels of competence and self-assurance. Universities and educational institutions can utilize this to develop more effective learning approaches, particularly in times of urgency like the COVID-19 pandemic. Subsequent investigations should explore possible mediators impacting the correlation between learning styles and student aptitude and self-assurance.